The Synthesis and Characterizations of CeY0.15Er0.05O2 Nanocrystal - Özlü Torun, Handan (Physics and Chemistry of Solid State, 2021)
CeY0.15Er0.05O2 nanocrystal powders prepared via sol-gel method. Phases identification have been made X-ray diffraction, SEM-EDX, FTIR, thermal and impedance analysis. XRD data show that all powders were obtained with cubic fluorite structure. With the increase of sintering temperature, the unit cell size decreased and the crystal size increased. The particle size was found to be in the range of 150 to 270 nm. It was found that the nitrates and organic species seen in the FTIR results. It was observed that organic species disappeared at sintering temperatures selected according to thermal analysis results. Impedance measurements of the pelletized sample were made. Although the crystal structure properties were good, it was found that the conductivity values were low.